Transdermal preparations

JP7633227B2Active Publication Date: 2025-02-19SUMITOMO PHARMA CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022501956
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-08-05
Filing Date
2021-02-18
Publication Date
2025-02-19
Estimated Expiration
2041-02-18

AI Technical Summary

Benefits of technology

【0008】 本発明によれば、製剤中のタンドスピロン又はその薬学的に許容される塩の皮膚透過性に優れ、使用時はタンドスピロンの薬効が発揮されるのに十分な血中濃度が維持できるタンドスピロン含有経皮吸収製剤を提供することができる。さらに、製剤中のタンドスピロン又はその薬学的に許容される塩の熱、湿度及び光に対する保存安定性が良好であり、製造性や品質管理が容易なタンドスピロン含有経皮吸収製剤を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007633227000001
    Figure 0007633227000001
  • Figure 0007633227000002
    Figure 0007633227000002
  • Figure 0007633227000003
    Figure 0007633227000003
Patent Text Reader

Abstract

The present invention pertains to a transdermal absorption preparation that is capable of maintaining a blood concentration sufficient to exert the medicinal effect of tandospirone and that has excellent storage stability against heat, humidity and light. The present invention makes it possible to provide a transdermal absorption preparation characterized by comprising tandospirone or a pharmaceutically acceptable salt thereof and levulinic acid. This transdermal absorption preparation of tandospirone exhibits high skin permeability of tandospirone or a pharmaceutically acceptable salt thereof contained in the preparation and has excellent storage stability against heat and light.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a transdermal preparation containing tandospirone or a pharma- ceutically acceptable salt thereof. [Background technology]

[0002] (1R,2S,3R,4S)-N-[4-[4-(pyrimidin-2-yl)piperazin-1-yl]butyl]-2,3-bicyclo[2.2.1]heptanedicarboximide (generic name "tandospirone") is a selective serotonin 1A receptor agonist, and tandospirone citrate tablets (trade name: Sedir (registered trademark) tablets) are commercially available in Japan as an anti-anxiety drug.

[0003] Patent Documents 1 to 3 disclose transdermal preparations containing tandospirone. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-228414 [Patent Document 2] WO2005 / 117886 publication [Patent Document 3] WO2008 / 044336 publication Summary of the Invention [Problem to be solved by the invention]

[0005] The present invention provides a transdermal preparation containing tandospirone which has improved skin permeability of tandospirone and excellent storage stability. [Means for solving the problem]

[0006] As a result of extensive research, the present inventors have found that the incorporation of levulinic acid improves the skin permeability of tandospirone, making it possible to reduce the amount of tandospirone-containing transdermal formulation that can be applied or sprayed, or to reduce the area of ​​the formulation. They have also found that the combined use of levulinic acid and a specific additive (iii) produces a synergistic effect in improving the skin permeability of tandospirone. As a result of further intensive research, the present inventors have found that by incorporating a specific additive (iv), a transdermal preparation having good stability while maintaining the improved skin permeability of tandospirone can be obtained. The present invention is also superior in this respect.

[0007] That is, the present invention is as follows. [1] A percutaneous absorption preparation having a percutaneous absorption layer, the percutaneous absorption layer comprising: (i) tandospirone or a pharma- ceutically acceptable salt thereof, and (ii) Levulinic acid or a pharma- ceutically acceptable salt thereof. A percutaneous absorption preparation comprising the above component (hereinafter, also referred to as "the percutaneous absorption preparation of the present invention"). [2] The transdermal absorption preparation according to the above item [1], which is in the form of a patch preparation (hereinafter, also referred to as "the patch preparation of the present invention"). [3] The percutaneous absorption preparation according to the above-mentioned [1] or [2], further comprising (iii) one or more additives selected from the group consisting of polyhydric alcohol fatty acid esters and fatty acid amides. [4] The percutaneous absorption preparation according to any one of the above-mentioned [1] to [3], wherein the percutaneous absorption layer further contains oleic acid. [5] The transdermal absorption preparation according to any one of the above-mentioned [1] to [4], further comprising (iv) one or more additives selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-mercaptobenzimidazole, propyl gallate, α-tocopherol, sodium sulfite and sodium hydrogen sulfite. [6] The percutaneous absorption preparation according to any one of the above-mentioned [1] to [5], wherein (i) is tandospirone. [7] The percutaneous absorption preparation according to any one of the above-mentioned [1] to [6], wherein (ii) is levulinic acid. [8] The percutaneous absorption preparation according to any one of the above [5] to [7], wherein (iv) contains 2,6-di-tert-butyl-4-methylphenol. [9] The percutaneous absorption preparation according to any one of the above-mentioned [5] to [8], wherein (iv) contains 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate.

[10] The percutaneous absorption preparation according to any one of the above-mentioned [3] to [9], wherein (iii) contains a polyhydric alcohol fatty acid ester.

[11] The percutaneous absorption preparation according to any one of the above-mentioned [3] to

[10] , wherein (iii) contains a propylene glycol fatty acid ester.

[12] The transdermal absorption preparation according to any one of the above-mentioned [1] to

[11] , further comprising (v) a monohydric alcohol fatty acid ester.

[13] The transdermal absorption preparation according to the above-mentioned

[12] , wherein the (v) monohydric alcohol fatty acid ester is isopropyl myristate and / or isopropyl palmitate.

[14] The percutaneous absorption preparation according to any one of the above-mentioned [1] to

[13] , wherein the content of (i) in 100% by weight of the percutaneous absorption layer is 0.1 to 30% by weight.

[15] The percutaneous absorption preparation according to any one of the above-mentioned [1] to

[14] , wherein the content of (ii) in 100% by weight of the percutaneous absorption layer is 0.1 to 20% by weight.

[16] The percutaneous absorption preparation according to any one of the above-mentioned [1] to

[14] , wherein the content of (ii) in 100% by weight of the percutaneous absorption layer is 3 to 10% by weight.

[17] The percutaneous absorption preparation according to any one of the above-mentioned [1] to

[14] , wherein the content of (ii) in 100% by weight of the percutaneous absorption layer is 6 to 7% by weight.

[18] The percutaneous absorption preparation according to any one of the above-mentioned [5] to

[17] , wherein the content of 2,6-di-tert-butyl-4-methylphenol (iv) in 100% by weight of the percutaneous absorption layer is 0.001 to 10% by weight.

[19] The percutaneous absorption preparation according to any one of the above-mentioned [5] to

[18] , wherein the content of sodium thiosulfate (iv) in 100% by weight of the percutaneous absorption layer is 0.001 to 7% by weight as the anhydride.

[20] The percutaneous absorption preparation according to any one of the above-mentioned [5] to

[19] , wherein the content of 2-mercaptobenzimidazole (iv) in 100% by weight of the percutaneous absorption layer is 0.001 to 5% by weight. [twenty one] The transdermal absorption preparation according to any one of the above-mentioned [5] to

[20] , wherein the content of propyl gallate (iv) in 100% by weight of the transdermal absorption layer is 0.001 to 7% by weight. [twenty two] The percutaneous absorption preparation according to any one of the above-mentioned [3] to

[21] , wherein the content of the polyhydric alcohol fatty acid ester (iii) in 100% by weight of the percutaneous absorption layer is 1 to 20% by weight. [twenty three] The percutaneous absorption preparation according to any one of the above-mentioned [2] to

[22] , wherein the percutaneous absorption preparation is a patch preparation and the percutaneous absorption layer is an adhesive layer. [twenty four] The transdermal absorption preparation according to the above-mentioned

[23] , wherein the pressure-sensitive adhesive layer contains an acrylic polymer, and the weight ratio of the acrylic polymer to the organic liquid component in the pressure-sensitive adhesive layer is 1:2.33 to 1:0.25. [twenty five] (i) A transdermal absorption preparation comprising tandospirone or a pharma- ceutically acceptable salt thereof, and one or more additives selected from the group consisting of aprotic polar solvents, organic acids (excluding levulinic acid and acetic acid), nonionic surfactants, and higher alcohol esters.

[26] The percutaneous absorption preparation according to the above

[25] , wherein the organic acid is oleic acid.

[27] A transdermal formulation comprising (i) tandospirone or a pharma- ceutically acceptable salt thereof, and (iv) one or more additives selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-mercaptobenzimidazole, propyl gallate, α-tocopherol, sodium sulfite, and sodium bisulfite.

[28] A composition for stabilizing a pharmaceutical comprising (i) tandospirone or a pharma- ceutically acceptable salt thereof, and (ii) levulinic acid or a pharma- ceutically acceptable salt thereof, comprising at least one component selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-mercaptobenzimidazole, propyl gallate, α-tocopherol, sodium sulfite, and sodium bisulfite.

[29] A composition for improving the skin permeability of (i) tandospirone or a pharma- ceutically acceptable salt thereof, comprising (ii) levulinic acid or a pharma- ceutically acceptable salt thereof, and (iii) a polyhydric alcohol fatty acid ester or a fatty acid amide. Effect of the Invention

[0008] According to the present invention, there can be provided a tandospirone-containing transdermal preparation which has excellent skin permeability of tandospirone or a pharma- ceutically acceptable salt thereof in the preparation and can maintain a sufficient blood concentration of tandospirone to exert its pharmacological effect during use.Furthermore, there can be provided a tandospirone-containing transdermal preparation which has good storage stability of tandospirone or a pharma- ceutically acceptable salt thereof in the preparation against heat, humidity and light, and which is easy to manufacture and to control the quality of. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Preferred embodiments of the present invention will now be described in detail.

[0010] In the present invention, the dosage form of the transdermal preparation is not particularly limited as long as it is a dosage form that has been used as a conventional external preparation.For example, the dosage forms described in the 17th revised Japanese Pharmacopoeia can be mentioned, and preferably, ointments, creams, gels, gel-like creams, sprays (e.g., external aerosols, pump sprays), external liquids (liniments and lotions) and patch preparations, more preferably, ointments or patch preparations, and even more preferably, patch preparations.

[0011] The patch preparation means a preparation that is applied to the skin in general. In the present invention, the shape of the patch preparation is not limited, and may be, for example, a tape, a sheet, etc. Specific examples of the patch preparation include a tape preparation, a patch preparation, a cataplasm preparation, a plaster preparation, etc.

[0012] Generally, patch preparations have a sheet-like structure consisting of three layers: a support, an adhesive layer, and a release film (liner). Nonwoven fabrics, knits, plastic films, etc. are used as the support. The adhesive layer is the main component that contains the active ingredient and adhesive and has a moderate adhesive strength. The release film is a covering that protects the adhesive surface of the adhesive layer until use, and polypropylene, polyethylene, cellophane, polyester, release paper, etc. are used. The adhesive layer is usually stored in a structure sandwiched between the support and the release film, and is used by peeling off the release film and attaching the adhesive surface of the adhesive layer to the skin.

[0013] The percutaneous absorption layer in the present invention means the composition of the part that directly contacts the skin. When the percutaneous absorption preparation is an ointment, cream, gel, gel-like cream, lotion, spray, aerosol, or liniment, the percutaneous absorption layer is the preparation composition itself. The percutaneous absorption layer contains (i) tandospirone or a pharma- ceutically acceptable salt thereof. It may further contain additives (ii), (iii), (iv), (v) and / or other additives. When the transdermal absorption preparation is a patch preparation, the transdermal absorption layer means an adhesive layer. The adhesive layer contains (i) tandospirone or a pharma- ceutically acceptable salt thereof, and an adhesive base. It may further contain additives (ii), (iii), (iv), (v) and / or other additives.

[0014] (Active ingredient drug) (i) The active ingredient drug contained in the transdermal absorption preparation of the present invention, (1R,2S,3R,4S)-N-[4-[4-(pyrimidin-2-yl)piperazin-1-yl]butyl]-2,3-bicyclo[2.2.1]heptanedicarboximide (generic name "tandospirone"), is represented by the following formula:

[0015] [ka]

[0016] The compound represented by the formula (hereinafter, also referred to as "Compound A") is a selective serotonin 1A receptor agonist. Tandospirone citrate is commercially available as an anxiolytic drug (Sedir (registered trademark) tablets).

[0017] The active ingredient drug of the present invention may be compound A (tandospirone free base) or a pharma- ceutical acceptable salt thereof. Examples of the pharma-ceutical acceptable salt include salts with organic acids such as formate, acetate, propionate, succinate, lactate, malate, adipate, citrate, tartrate, methanesulfonate, fumarate, maleate, p-toluenesulfonate, and ascorbate; salts with inorganic acids such as hydrochloride, hydrobromide, sulfate, nitrate, and phosphate. Compound A or a pharma-ceutical acceptable salt thereof may be either a solvate (e.g., hydrate, ethanol solvate, propylene glycol solvate) or a non-solvate.

[0018] The above-mentioned compound A or a pharma- ceutically acceptable salt thereof can be produced, for example, by the method described in JP-A-58-126865 or a method equivalent thereto. The produced compound A or a pharma-ceutically acceptable salt thereof may be appropriately pulverized by a commonly used method.

[0019] The content of "compound A or a pharma- ceutically acceptable salt thereof" contained in the transdermal absorption preparation of the present invention is not particularly limited since it must be set depending on the age, symptoms, etc. of the patient to be administered. However, the content, calculated as compound A (tandospirone free base), is usually about 0.1 to about 30% by weight, preferably about 0.1 to about 20% by weight, and more preferably about 0.1 to about 15% by weight, based on 100% by weight of the transdermal absorption layer. When the percutaneous absorption preparation is a patch preparation, the amount is usually about 0.1 to about 30% by weight, preferably about 0.1 to about 20% by weight, more preferably about 0.1 to about 15% by weight, even more preferably 1 to 10% by weight, and still more preferably 2 to 8% by weight, based on 100% by weight of the adhesive layer, depending on the area of ​​the patch preparation. Here, "converted to compound A" means that when compound A is in the form of a salt or when compound A has water of crystallization, the salt or the amount equivalent to the water of crystallization is not included in the weight of compound A. In other words, it means that a salt of compound A or a hydrate thereof is calculated by replacing it with the weight of an equimolar amount of compound A (free base nonhydrate).

[0020] (Levulinic acid) The levulinic acid used in the present invention is an organic acid classified as a keto acid. The levulinic acid used in the present invention is a free acid of levulinic acid (i.e., levulinic acid itself), and the additive (ii) used in the present invention may be a free acid of levulinic acid (i.e., levulinic acid itself) or may be provided as a pharmaceutically acceptable salt thereof. Examples of pharmaceutically acceptable salts include alkali metal salts such as sodium salts and potassium salts. As levulinic acid or a pharmaceutically acceptable salt thereof, a commercially available product may be used as it is, or a pharmaceutically acceptable salt thereof prepared from levulinic acid according to a method known per se may be used. As (ii) levulinic acid or a pharmaceutically acceptable salt thereof used in the present invention, levulinic acid is preferred.

[0021] In the percutaneous absorption preparation of the present invention, if the content of levulinic acid or a pharma- ceutically acceptable salt thereof in the percutaneous absorption layer is too small, the effect of promoting the skin permeability of the drug (i.e., compound A or a pharma- ceutically acceptable salt thereof) tends to be insufficient, or a part of compound A or a pharma- ceutical acceptable salt thereof tends to become crystalline during production or storage. If the content of levulinic acid or a pharma- ceutical acceptable salt thereof in the percutaneous absorption layer is too large, the skin irritation tends to increase. Therefore, the content of levulinic acid or a pharma- ceutical acceptable salt thereof in the percutaneous absorption layer is preferably 0.1 to 20 wt%, more preferably 0.5 to 15 wt%, even more preferably 1 to 10 wt%, and most preferably 3 to 8 wt%, in terms of levulinic acid (free acid of levulinic acid) in 100 wt% of the percutaneous absorption layer. From the viewpoint of promoting the skin permeability of the drug, it is preferably 0.5 wt% or more, more preferably 1 wt% or more, and even more preferably 3 wt% or more. From the viewpoint of skin irritation, the content is preferably 15% by weight or less, more preferably 10% by weight or less. Specifically, the content of levulinic acid or a pharma- ceutically acceptable salt thereof in the transdermal absorption layer, calculated as levulinic acid (free acid of levulinic acid), can be 0.1% by weight, 0.5% by weight, 1% by weight, 3% by weight, 4% by weight, 5% by weight, or 6% by weight as the lower limit, and 20% by weight, 15% by weight, 10% by weight, 8% by weight, or 7% by weight as the upper limit, in 100% by weight of the transdermal absorption layer. Here, "converted to levulinic acid" means that when levulinic acid is in the form of a salt, the amount of the salt is not included in the weight of levulinic acid. In other words, it means that the salt of levulinic acid is calculated by replacing it with the weight of an equimolar amount of levulinic acid (free acid).

[0022] When the transdermal absorption preparation is a patch preparation, the content of levulinic acid or a pharma- ceutically acceptable salt thereof in 100% by weight of the "transdermal absorption layer" can be read as the content of levulinic acid or a pharma- ceutically acceptable salt thereof in the "adhesive layer."

[0023] (Polyhydric alcohol fatty acid esters and fatty acid amides) The additive (iii) used in the present invention can be selected from the group consisting of polyhydric alcohol fatty acid esters and fatty acid amides. Preferably, one or more selected from polyhydric alcohol fatty acid esters can be used. Examples of polyhydric alcohol fatty acid esters include polyoxyethylene sorbitan fatty acid esters, sorbitan fatty acid esters, polyoxyethylene fatty acid esters, glycerin fatty acid esters, propylene glycol fatty acid esters, etc. Among these, glycerin fatty acid esters, propylene glycol fatty acid esters, and diethylene glycol fatty acid esters are preferred, glycerin fatty acid esters and propylene glycol fatty acid esters are more preferred, and propylene glycol fatty acid esters are particularly preferred. Examples of fatty acid amides include lauric acid diethanolamide and coconut oil fatty acid N-methylethanolamide.

[0024] Examples of glycerin fatty acid esters include glycerol tricaprylate, glycerol caprate, glycerol triacetate, glyceryl monocaprylate, glyceryl caprylate, glyceryl oleate, glyceryl stearate, glycerol monolinoleate, glycerol monooleate, and glycerol stearate. Examples of propylene glycol fatty acid esters include propylene glycol dicaprate, propylene glycol dilaurate, propylene glycol monolaurate, and propylene glycol monocaprylate (preferably propylene glycol monolaurate and propylene glycol monocaprylate). The polyhydric alcohol fatty acid esters can be used alone or in combination of two or more.

[0025] In the percutaneous absorption preparation of the present invention, the content of the polyhydric alcohol fatty acid ester or fatty acid amide in the percutaneous absorption layer is not particularly limited, but is preferably 1 to 20% by weight based on 100% by weight of the percutaneous absorption layer. From the viewpoint of skin irritation, the content of the polyhydric alcohol fatty acid ester or fatty acid amide in the percutaneous absorption layer is more preferably 1 to 15% by weight based on 100% by weight of the percutaneous absorption layer. Specifically, the content of polyhydric alcohol fatty acid ester or fatty acid amide in the transdermal absorption layer can be, relative to 100% by weight of the transdermal absorption layer, as lower limits of 1 wt%, 1.5 wt%, 3 wt%, or 5 wt%, and as upper limits of 20 wt%, 18 wt%, 15 wt%, or 13 wt%.

[0026] When the transdermal absorption preparation is a patch preparation, the content of polyhydric alcohol fatty acid ester or fatty acid amide in 100% by weight of the "transdermal absorption layer" can be read as the content of polyhydric alcohol fatty acid ester or fatty acid amide in the "adhesive layer."

[0027] The additive components used in the present invention, consisting of (ii) levulinic acid and (iii) polyhydric alcohol fatty acid ester or fatty acid amide, are hereinafter referred to as "Additive Group A". The combination of these "Additive Group A" exhibited an effect of enhancing the skin permeation of Compound A or a pharma- ceutically acceptable salt thereof.

[0028] (Stabilizer) The additive (iv) used in the present invention (hereinafter, sometimes referred to as "additive group B") can be selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-mercaptobenzimidazole, propyl gallate, α-tocopherol, sodium sulfite and sodium hydrogen sulfite. The additive group B is preferably selected from 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate and 2-mercaptobenzimidazole, more preferably selected from 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate. The stabilizing effect of compound A or a pharma- ceutically acceptable salt thereof in the formulation can be obtained by adding only one additive included in additive group B, but can also be obtained by adding two or more additives selected from additive group B in combination. In particular, a combination of 2,6-di-tert-butyl-4-methylphenol and two or more selected from sodium thiosulfate and 2-mercaptobenzimidazole is preferred because it provides a synergistic stabilizing effect of compound A in the formulation. Here, the stabilizing effect means an effect of improving the stability (storage stability) of compound A in the percutaneous absorption formulation of the present invention against heat, humidity, and / or light, and includes, for example, an effect of suppressing the decrease in the content of compound A when heated at 40°C, 50°C, and 60°C for a certain period of time during the preparation or storage, when humidified for a certain period of time (25°C 60% RH, 40°C 75% RH conditions, etc.), when exposed to light for a certain period of time, an effect of suppressing the generation of related substances, and an effect of suppressing discoloration of the formulation.

[0029] If the content of the additives of the additive group B in the transdermal absorption layer is too low, the stabilizing effect of compound A or its pharma- ceutically acceptable salt tends to be insufficient, and if it is too high, the additives of the additive group B in the transdermal absorption layer separate from other components, which causes problems in the production of the patch preparation. For this reason, the content of the additives of the additive group B in the transdermal absorption layer is preferably 0.001 to 10% by weight in 100% by weight of the transdermal absorption layer. The content of 2,6-di-tert-butyl-4-methylphenol is usually 0.001 to 10% by weight in 100% by weight of the transdermal absorption layer, preferably 0.005 to 10% by weight, more preferably 0.01 to 10% by weight, and even more preferably 0.01 to 8% by weight. The content of sodium thiosulfate is usually 0.001 to 7% by weight, preferably 0.001 to 5% by weight, more preferably 0.001 to 3% by weight, and even more preferably 0.001 to 2% by weight, in 100% by weight of the transdermal absorption layer. The content of 2-mercaptobenzimidazole is usually 0.001 to 5% by weight, preferably 0.05 to 5% by weight, and more preferably 0.1 to 5% by weight, in 100% by weight of the transdermal absorption layer. The content of propyl gallate is preferably 0.001 to 7% by weight, and more preferably 0.001 to 5% by weight, in 100% by weight of the transdermal absorption layer. In addition, when additives of additive group B are used in combination, the total content of two or more additives selected from additive group B is preferably 0.002 to 15% by weight, and more preferably 0.005 to 10% by weight, in 100% by weight of the transdermal absorption layer. When 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate are contained, the total content is preferably 0.002 to 10% by weight, more preferably 0.002 to 8% by weight, based on 100% by weight of the transdermal absorption layer. The total content of 2,6-di-tert-butyl-4-methylphenol and 2-mercaptobenzimidazole is preferably 0.05 to 10% by weight, based on 100% by weight of the transdermal absorption layer. As the content ratio of the combination of these additives, the content ratio of 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate is preferably 1:0.001 to 1:1000, more preferably 1:0.005 to 1:500, and even more preferably 1:0.01 to 1:50, by weight. The content ratio of 2,6-di-tert-butyl-4-methylphenol and 2-mercaptobenzimidazole is preferably 1:0.01 to 1:500, more preferably 1:0.1 to 1:100, and even more preferably 1:0.5 to 1:50, by weight.

[0030] When the transdermal absorption preparation is a patch preparation, the content of additive group B in 100% by weight of the "transdermal absorption layer" can be read as the content of additive group B in the "adhesive layer."

[0031] (Organic liquid component) In the patch preparation of the present invention, from the viewpoint of making the adhesive layer more flexible and reducing physical skin irritation during application and / or removal, the adhesive layer preferably contains an organic liquid component.

[0032] In the patch preparation of the present invention, from the viewpoint of softening the adhesive layer and reducing physical skin irritation during application and / or removal, the weight ratio (weight % ratio of adhesive base to total organic liquid component) of the total content of adhesive base and organic liquid component in the adhesive layer is preferably 1:2.33 to 1:0.25, and from the viewpoint of manufacturability, more preferably 1:2.33 to 1:0.66. Furthermore, since an increase in the component ratio of adhesive base in the adhesive layer improves adhesiveness and also improves skin irritation during removal, from the viewpoint of skin adhesion, the total content ratio of adhesive base and organic liquid component is more preferably 1:1.86 to 1:0.66, and from the viewpoint of skin irritation, more preferably 1:1.86 to 1:1.

[0033] In the patch preparation of the present invention, from the viewpoint of softening the adhesive layer and reducing physical skin irritation during application and / or removal, the weight ratio (weight % ratio of acrylic polymer to total organic liquid component) of the total content of the acrylic polymer to total organic liquid component in the adhesive layer is preferably 1:2.33 to 1:0.25. From the viewpoint of skin adhesion, the weight ratio (weight % ratio) of the total content of the acrylic polymer to total organic liquid component in the adhesive layer is preferably 1:1.86 to 1:0.66.

[0034] In the present invention, the total weight of the organic liquid components means the total weight of components that correspond to "liquid", "liquid (partially precipitated)", "liquid", "oily" or "soft paste" within the range of 25° C.±5° C., as described below. The organic liquid components including the specific examples described below are calculated as the organic liquid components.

[0035] The organic liquid component in the present invention is an organic substance that is liquid at room temperature (25°C), exhibits the action of plasticizing the adhesive layer, and is compatible with the adhesive polymer constituting the above-mentioned adhesive. Here, the term "liquid" means that it can be used as a liquid by appropriately warming it to a degree that does not impair the quality in formulation, and is used in the sense of including not only those that are liquid at 25°C, but also those that are partially precipitated or partially solidified. For example, in the instruction manual of a specific additive (commercially available product) described later, those described as "Liquid", "Liquid", "Liquid (partially precipitated)", "Liquid", "Oily", or "Soft paste-like" within the range of 25°C ± 5°C are included in the "liquid" in this specification.

[0036] In the present invention, specific examples of the organic liquid component include fatty acid esters of fatty acids having 8 to 18 carbon atoms (preferably 12 to 16 carbon atoms) and monohydric alcohols having 1 to 18 carbon atoms, such as isopropyl myristate, ethyl laurate, isopropyl palmitate, ethyl oleate, isostearyl laurate, isotridecyl myristate, octyl palmitate, diisopropyl adipate, cetyl lactate, oleyl oleate, cetyl ethylhexanoate, octyldodecyl myristate, butyl stearate, 2-ethylhexyl stearate, n-butyl acetate, and diethyl sebacate (hereinafter also abbreviated as "C8-18(12-16)-C1-18 fatty acid ester").); fatty acid esters of fatty acids having 8 to 18 carbon atoms and polyhydric alcohols having 1 to 18 carbon atoms, such as glycerin fatty acid esters, propylene glycol fatty acid esters, polyethylene glycol fatty acid esters, and sucrose fatty acid esters; fatty acid amides, such as lauric acid diethanolamide and coconut oil fatty acid N-methylethanolamide; organic acids, such as fatty acids (e.g., caprylic acid (octanoic acid, C8), caproic acid, pelargonic acid (nonanoic acid, C9), acetic acid, propionic acid, isobutyric acid, levulinic acid, lactic acid, and oleic acid), and alkylsulfonic acids (methanesulfonic acid, ethanesulfonic acid, and polyoxyethylene ether sulfonic acid); glycols, such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, 1,3-propanediol, and polypropylene glycol; oils and fats, such as olive oil, castor oil, coconut oil, sesame oil, and squalene; dimethyl sulfoxide, dimethylformamide, dimethylacetamide, dimethyl Organic solvents such as ethyl laurylamide, dodecyl pyrrolidone, isosorbitol, oleyl alcohol, lauric acid, and N-methyl-2-pyrrolidone; sodium polyoxyethylene alkyl ether sulfate, sodium polyoxyethylene lauryl ether sulfate, sodium alkyl naphthalene sulfonate, polyoxyethylene oleylamine, sodium polyoxyethylene oleyl ether phosphate, polyoxyl stearate, decaglyceryl laurate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monostearate, polyoxyethylene lauryl ether (lauromoclogol), sorbitan monolaurate, sorbitan trioleate, polyoxyethylene sorbit tetraoleate, glycerol monooleate, and tocopherol; hydrocarbons such as gelled hydrocarbons and liquid paraffin; known plasticizers; and other organic liquid components such as ethoxylated stearyl alcohol and glycerin. The organic liquid components can be used alone or in combination of two or more. The organic liquid component in the present invention preferably contains a C8-18(12-16)-C1-18 fatty acid ester, and particularly preferably contains isopropyl myristate or isopropyl palmitate.

[0037] (Crosslinking agent) In the patch preparation of the present invention, the adhesive layer can be crosslinked. The crosslinking is not particularly limited, and can be performed by a method generally used in the art, such as chemical crosslinking (crosslinking using a crosslinking agent, etc.) and physical crosslinking (crosslinking by electron beam irradiation such as gamma rays or ultraviolet light irradiation, etc.). The crosslinking makes the adhesive layer into a so-called gel-state adhesive layer, which gives a soft feel to the skin and has appropriate adhesiveness and cohesive strength. In the patch preparation of the present invention, when the adhesive layer is subjected to chemical crosslinking or physical crosslinking, the stability of compound A or a pharma- ceutical acceptable salt thereof during the preparation manufacturing process or storage is likely to decrease (i.e., the amount of analogous substances produced tends to increase). In the present invention, it has been confirmed that the stability of compound A or a pharma- ceutical acceptable salt thereof is improved by blending the additive group B in the crosslinked acrylic polymer.

[0038] When the adhesive layer is subjected to a chemical crosslinking treatment using a crosslinking agent, it is possible to cause self-crosslinking in the adhesive layer, but crosslinking can be effectively caused by including a crosslinking agent in the adhesive layer. Such crosslinking agents are not particularly limited as long as they are crosslinking agents whose crosslinking formation is not inhibited by compound A or a pharma- ceutically acceptable salt thereof, and examples thereof include peroxides (e.g., benzoyl peroxide (BPO) and the like), isocyanate compounds, organometallic compounds (e.g., zirconium, zinc, zinc acetate, and the like), metal alcoholates (e.g., tetraethyl titanate, tetraisopropyl titanate, aluminum isopropylate, aluminum sec-butylate, and the like), metal chelate compounds (e.g., aluminum ethyl acetoacetate diisopropylate, dipropoxybis(acetylacetonate) titanium, tetraoctylene glycol titanium, aluminum isopropylate, ethyl acetoacetate aluminum diisopropylate, aluminum tris(ethyl acetoacetate), aluminum tris(acetylacetonate)), and the like. In particular, as the crosslinking agent to be contained in the adhesive layer, a metal chelate compound is preferred from the viewpoint of reducing the decrease in cohesive strength of the adhesive layer when the patch preparation of the present invention is applied to human skin and making it difficult for cohesive failure to occur when the adhesive layer is peeled off. The crosslinking agent may be used alone or in combination of two or more kinds.

[0039] When the adhesive layer is subjected to a chemical crosslinking treatment using a crosslinking agent, the amount of the crosslinking agent varies depending on the type of crosslinking agent and adhesive polymer, but is usually preferably 0.01 to 10 wt%, more preferably 0.05 to 5 wt%, based on 100 wt% of the adhesive layer. If the amount of the crosslinking agent is less than 0.01 wt% based on 100 wt% of the adhesive layer, the adhesive layer cannot be given sufficient cohesive strength due to too few crosslinking points, and there is a risk of adhesive residue or strong skin irritation occurring due to cohesive failure when the patch preparation is peeled off from the skin. If the amount of the crosslinking agent is more than 10 wt% based on 100 wt% of the adhesive layer, the cohesive strength is high, but sufficient skin adhesion may not be obtained. In addition, there is a risk of skin irritation occurring due to the remaining unreacted crosslinking agent. The chemical crosslinking treatment can be carried out, for example, by adding a crosslinking agent to the pressure-sensitive adhesive layer, followed by a step of heating to a crosslinking reaction temperature or higher and storing the mixture, i.e., an aging step, and the heating temperature is appropriately selected depending on the type of crosslinking agent, but is preferably 60 to 90° C., more preferably 60 to 80° C. The heating time is preferably 12 to 96 hours, more preferably 24 to 72 hours.

[0040] In the present invention, the aprotic polar solvent is not particularly limited, but can be selected from, for example, N-methyl-2-pyrrolidone, dimethylacetamide, dimethyllaurylamide, and the like. The nonionic surfactant is not particularly limited, but may be selected from, for example, lauromacrogol, sorbitan monolaurate, polysorbate 80, polysorbate 20, and the like. The organic acid (excluding levulinic acid and acetic acid) is not particularly limited as long as it is other than levulinic acid and acetic acid, and examples thereof include fatty acids, aromatic carboxylic acids, alkylsulfonic acids, and cholic acid derivatives. Specifically, examples of fatty acids include propionic acid, citric acid, isobutyric acid, caproic acid, caprylic acid, lactic acid, maleic acid, oleic acid, pyruvic acid, oxalic acid, succinic acid, and tartaric acid. Examples of aromatic carboxylic acids include phthalic acid, salicylic acid, benzoic acid, and acetylsalicylic acid. Examples of alkylsulfonic acids include methanesulfonic acid, ethanesulfonic acid, propylsulfonic acid, butanesulfonic acid, and polyoxyethylene alkyl ether sulfonic acid. Examples of cholic acid derivatives include dehydrocholic acid. The organic acid (excluding levulinic acid and acetic acid) is preferably a fatty acid, and particularly preferably oleic acid. The higher alcohol ester is not particularly limited, but may be selected from, for example, diisopropyl adipate, oleyl oleate, diethyl sebacate, and the like. The content of the aprotic polar solvent in the transdermal absorption layer is preferably 0.1 to 20% by weight, more preferably 0.5 to 15% by weight, and even more preferably 1 to 10% by weight, based on 100% by weight of the transdermal absorption layer. The content of the nonionic surfactant in the transdermal absorption layer is preferably 0.1 to 20% by weight, more preferably 0.5 to 15% by weight, and even more preferably 1 to 10% by weight, based on 100% by weight of the transdermal absorption layer. The content of the organic acid (excluding levulinic acid and acetic acid) in the transdermal absorption layer is preferably 0.1 to 30% by weight, more preferably 0.1 to 25% by weight, further preferably 0.1 to 20% by weight, further preferably 0.1 to 15% by weight, based on 100% by weight of the transdermal absorption layer. In another embodiment, the content is preferably 0.3 to 20% by weight, more preferably 0.3 to 10% by weight. In the percutaneous absorption preparation of the present invention, oleic acid in the percutaneous absorption layer is expected to prevent a part of compound A or a pharma- ceutical acceptable salt thereof from becoming crystalline during production or storage, and to reduce skin irritation during application. Oleic acid can be contained in a high proportion in the percutaneous absorption layer. Specifically, the content of oleic acid in the percutaneous absorption layer is preferably 0.1-30 wt%, more preferably 0.1-25 wt%, and even more preferably 0.3-20 wt%, based on 100 wt% of the percutaneous absorption layer. The content of oleic acid in the transdermal absorption layer, relative to 100% by weight of the transdermal absorption layer, can be as follows: lower limit: 0.1% by weight, 0.3% by weight, 0.5% by weight, 1% by weight, 1.5% by weight, 2% by weight, or 3% by weight; and upper limit: 30% by weight, 25% by weight, 20% by weight, 15% by weight, or 10% by weight. When the organic acid is oleic acid, the content ratio of levulinic acid to oleic acid in the transdermal absorption layer is preferably 1:20 to 20:1, more preferably 1:10 to 15:1, and even more preferably 1:5 to 10:1. The content of the higher alcohol ester in the transdermal absorption layer is preferably 0.1 to 30% by weight, more preferably 0.5 to 20% by weight, and even more preferably 1 to 15% by weight, based on 100% by weight of the transdermal absorption layer. By incorporating these additives, the skin permeability of compound A or a pharma- ceutical acceptable salt thereof can be improved.

[0041] (Ointment base) When the transdermal absorption preparation of the present invention is an ointment, the base of the ointment is not particularly limited, but examples thereof include oleaginous bases such as oils and fats, waxes (beeswax), paraffin, petrolatum, lanolin, hydrous lanolin, lanolin alcohol, and other hydrocarbons, and water-soluble bases such as macrogol.

[0042] (Transdermal absorption layer) In addition to the above-mentioned components, the percutaneous absorption layer of the percutaneous absorption preparation of the present invention may contain other pharma- ceutically acceptable additives used in the manufacture of percutaneous absorption preparations, if necessary, unless otherwise hindrance. Such ingredients are not particularly limited, but examples thereof include flavors, colorants, fillers, thickeners, pH regulators, emulsifiers, suspending agents, etc.

[0043] (Adhesive layer) The adhesive layer in the patch preparation of the present invention is formed on at least one side of the support and contains at least (i) compound A or a pharma- ceutically acceptable salt thereof and an adhesive base. The adhesive layer preferably further contains (ii) levulinic acid or a pharma- ceutically acceptable salt thereof. The adhesive layer may further contain (iii) a polyhydric alcohol fatty acid ester or fatty acid amide, and / or (iv) one or more additives selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-mercaptobenzimidazole, propyl gallate, α-tocopherol, sodium sulfite, and sodium hydrogen sulfite.

[0044] The thickness of the pressure-sensitive adhesive layer is not particularly limited as long as it is not extremely thick, but is preferably from 20 to 600 μm, more preferably from 30 to 300 μm, and even more preferably from 50 to 200 μm.

[0045] In addition to the above-mentioned components, the adhesive layer in the patch preparation of the present invention may contain other pharma- ceutically acceptable additives used in the manufacture of patch preparations, if necessary, unless otherwise hindrance. Such ingredients are not particularly limited, but examples thereof include flavors, colorants, fillers, thickeners, etc.

[0046] Examples of the flavoring agent include, but are not limited to, dl-menthol, orange oil, peppermint oil, lemon oil, rose oil, etc. Examples of the thickener include, but are not limited to, carboxymethylcellulose, carrageenan, pectin, poly(N-vinylacetamide), N-vinylacetamide-sodium acrylate copolymer, etc. Examples of the pH regulator include, but are not limited to, citric acid hydrate, glycine, acetic acid, tartaric acid, sodium hydrogen carbonate, lactic acid, etc. Examples of the emulsifier include, but are not limited to, oleyl alcohol, hydroxypropylcellulose, propylene glycol, propylene glycol fatty acid ester, etc. Examples of the suspending agent include, but are not limited to, carmellose sodium, glycerin fatty acid ester, polyoxyethylene hydrogenated castor oil 60, etc.

[0047] (Support) The patch preparation of the present invention comprises a support and an adhesive layer formed on at least one side of the support. That is, the support has a first side and a second side of a sheet-like structure, and an adhesive layer is formed on at least the first side. If necessary, a release sheet may be provided on the side of the adhesive layer opposite to the support. The shape of the patch preparation may be a sheet type of any shape or a roll-like shape.

[0048] (Adhesive base) In the patch preparation of the present invention, the formulation of the adhesive layer is not particularly limited, but the adhesive base may be, for example, an acrylic polymer, a rubber polymer, a silicone polymer, etc. These polymers may be used alone or in combination of two or more.

[0049] The acrylic polymer in the patch preparation of the present invention is preferably an acrylic polymer having a (meth)acrylic acid alkyl ester unit as the main constituent unit. For example, from the viewpoint of adhesiveness to human skin and solubility of drugs during preparation, the acrylic polymer having a (meth)acrylic acid alkyl ester as the main constituent unit is preferably a copolymer of a (meth)acrylic acid alkyl ester (first monomer component) and a vinyl monomer (second monomer component) having a functional group that can participate in a crosslinking reaction, or an acrylic polymer further copolymerized with another monomer (third monomer component) other than these.

[0050] In this specification, "(meth)acrylic" means both "acrylic" and "methacrylic".

[0051] Examples of the (meth)acrylic acid alkyl ester (first monomer component) include linear, branched, or cyclic alkyl groups having 1 to 18 carbon atoms (for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, sec-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, cyclohexyl, 3-methylpentyl, n-heptyl, cycloheptyl, n-octyl, 2-ethylhexyl, cyclooctyl, n-nonyl, cyclononyl, n-decyl, cyclodecyl, n-undecyl, n-dodecyl, n-tridecyl, n-tetradecyl, isotetradecyl, n-pentadecyl, n-hexadecyl, and the like). and the like), and the like in which the alkyl group is a linear, branched or cyclic alkyl group having 4 to 18 carbon atoms (for example, n-butyl, isobutyl, tert-butyl, sec-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, cyclohexyl, 3-methylpentyl, n-heptyl, cycloheptyl, n-octyl, 2-ethylhexyl, cyclooctyl, n-nonyl, cyclononyl, n-decyl, cyclodecyl, n-undecyl, n-dodecyl, n-tridecyl, and the like). In particular, since it is suitable to use a monomer component that lowers the glass transition temperature of the polymer in order to impart adhesion at room temperature, (meth)acrylic acid alkyl esters in which the alkyl group is a linear, branched, or cyclic alkyl group having 4 to 8 carbon atoms (e.g., n-butyl, isobutyl, tert-butyl, sec-butyl, n-pentyl, isopentyl, neopentyl, n-hexyl, isohexyl, cyclohexyl, 3-methylpentyl, n-heptyl, cycloheptyl, n-octyl, 2-ethylhexyl, cyclooctyl, etc.) are more preferred, and among these, (meth)acrylic acid alkyl esters in which the alkyl group is n-butyl, 2-ethylhexyl, or cyclohexyl are even more preferred.

[0052] Particularly preferred specific examples of the (meth)acrylic acid alkyl ester (first monomer component) include, for example, butyl acrylate, 2-ethylhexyl acrylate, 2-ethylhexyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and among these, 2-ethylhexyl acrylate is the most preferred. The (meth)acrylic acid alkyl ester (first monomer component) can be used alone or in combination of two or more kinds.

[0053] Examples of the vinyl monomer (second monomer component) having a functional group capable of participating in a crosslinking reaction using the crosslinking agent include vinyl monomers whose functional group capable of participating in a crosslinking reaction is, for example, a hydroxy group, a carboxy group, a vinyl group, etc., and among these, vinyl monomers whose functional group capable of participating in a crosslinking reaction is a hydroxy group or a carboxy group are preferred. Specific examples of the vinyl monomer (second monomer component) include, for example, (meth)acrylic acid hydroxyethyl ester, (meth)acrylic acid hydroxypropyl ester, (meth)acrylic acid, itaconic acid, maleic acid, maleic anhydride, mesaconic acid, citraconic acid, glutaconic acid, etc. Among these, from the viewpoint of easy availability, acrylic acid, methacrylic acid, or acrylic acid hydroxyethyl ester is preferred, and acrylic acid is most preferred. The vinyl monomer (second monomer component) can be used alone or in combination of two or more kinds.

[0054] The other monomer (third monomer component) is mainly used for adjusting the cohesive strength of the adhesive layer, adjusting the solubility and / or release of the drug (compound A or a pharma- ceutically acceptable salt thereof), etc. Examples of the other monomer (third monomer component) include vinyl esters such as vinyl acetate and vinyl propionate; vinyl ethers such as methyl vinyl ether and ethyl vinyl ether; vinyl amides such as N-vinyl-2-pyrrolidone and N-vinyl caprolactam; alkoxy group-containing monomers such as (meth)acrylic acid methoxyethyl ester, (meth)acrylic acid ethoxyethyl ester, and (meth)acrylic acid tetrahydrofurfuryl ester; hydroxy group-containing monomers such as hydroxypropyl (meth)acrylate and α-hydroxymethyl acrylate (such hydroxy group-containing monomers are not involved in the crosslinking reaction because they are used as the third monomer component); (meth)acrylic acid derivatives having an amide group such as (meth)acrylamide, dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, and N-methylol (meth)acrylamide; and (meth)acrylic acid aminoethyl ester. (meth)acrylic acid aminoalkyl esters such as (meth)acrylic acid dimethylaminoethyl ester and (meth)acrylic acid tert-butylaminoethyl ester; (meth)acrylic acid alkoxyalkylene glycol esters such as (meth)acrylic acid methoxyethylene glycol ester, (meth)acrylic acid methoxydiethylene glycol ester, (meth)acrylic acid methoxypolyethylene glycol ester and (meth)acrylic acid methoxypolypropylene glycol ester; (meth)acrylonitrile; monomers having a sulfo group such as styrenesulfonic acid, allylsulfonic acid, sulfopropyl (meth)acrylate, (meth)acryloyloxynaphthalenesulfonic acid, and acrylamidomethylsulfonic acid; vinyl group-containing monomers such as vinyl piperidone, vinylpyrimidine, vinylpiperazine, vinylpyrrole, vinylimidazole, vinyloxazole, and vinylmorpholine. Among them, vinyl esters (e.g., vinyl acetate) and vinylamides (e.g., N-vinyl-2-pyrrolidone) are preferred. The other monomer (third monomer component) can be used alone or in combination of two or more.

[0055] When the acrylic polymer in the patch preparation of the present invention is a copolymer of a (meth)acrylic acid alkyl ester (first monomer component) and a vinyl monomer (second monomer component) having a functional group capable of participating in a crosslinking reaction, the copolymerization ratio (first monomer component / second monomer component) is preferably 85-99% by weight / 1-15% by weight, more preferably 90-99% by weight / 1-10% by weight.

[0056] Furthermore, when the acrylic polymer in the patch preparation of the present invention is a copolymer of a (meth)acrylic acid alkyl ester (first monomer component), a vinyl monomer having a functional group capable of participating in a crosslinking reaction (second monomer component), and a monomer other than these (third monomer component), the copolymerization ratio (first monomer component / second monomer component / third monomer component) is preferably 35-94% by weight / 1-15% by weight / 5-50% by weight, more preferably 50-89% by weight / 1-10% by weight / 10-40% by weight.

[0057] The polymerization reaction using each of the monomer components may be carried out by a method known per se and is not particularly limited. For example, the monomers may be reacted in a solvent (e.g., ethyl acetate, etc.) in the presence of a polymerization initiator (e.g., benzoyl peroxide, azobisisobutyronitrile, etc.) at 50 to 70°C for 5 to 48 hours.

[0058] As the acrylic polymer in the patch preparation of the present invention, 2-ethylhexyl acrylate / acrylic acid / N-vinyl-2-pyrrolidone copolymer, 2-ethylhexyl acrylate / 2-hydroxyethyl acrylate / vinyl acetate copolymer, 2-ethylhexyl acrylate / acrylic acid copolymer, etc. are preferred, with 2-ethylhexyl acrylate / acrylic acid / N-vinyl-2-pyrrolidone copolymer being particularly preferred.

[0059] The glass transition temperature of the acrylic polymer in the patch preparation of the present invention varies depending on the copolymer composition, but from the viewpoint of adhesiveness as a patch preparation, it is preferably −100 to −10° C., more preferably −90 to −20° C. The glass transition temperature is a value measured with a differential scanning calorimeter.

[0060] Examples of the rubber polymer in the patch preparation of the present invention include styrene-isoprene-styrene block copolymer, isoprene rubber, polyisobutylene, styrene-butadiene-styrene block copolymer, styrene-ethylene-butylene-styrene block copolymer, styrene-ethylene-propylene-styrene block copolymer, styrene-butadiene rubber, etc. Among them, styrene-isoprene-styrene block copolymer and polyisobutylene are preferred, and styrene-isoprene-styrene block copolymer is more preferred. The rubber polymer can be used alone or in combination of two or more kinds.

[0061] The silicone polymer in the patch preparation of the present invention may be, for example, one that contains a polyorganosiloxane such as silicone rubber, dimethylsiloxane base, diphenylsiloxane base, or polydimethylsiloxane as the main component and a tackifier such as MQ resin, etc. The silicone polymer may be used alone or in combination of two or more kinds.

[0062] In the patch preparation of the present invention, the content of the adhesive base in the adhesive layer is preferably 30-80 wt %, more preferably 40-70 wt %, based on 100 wt % of the adhesive layer.

[0063] (Release liner) In the patch preparation of the present invention, the surface of the adhesive layer opposite to the support (the surface to be applied to the skin) is preferably laminated with a release liner until the preparation is actually used. The release liner is not particularly limited, and any known release liner can be used. Specifically, for example, a release liner in which a release treatment agent layer made of a release treatment agent is formed on the surface of a substrate for a release liner, a plastic film that has high releasability, a release liner in which a release layer made of the material of the plastic film with high releasability is formed on the surface of a substrate for a release liner, etc. can be mentioned. The release surface of the release liner may be only one side of the substrate, or both sides.

[0064] In such a release liner, the release treatment agent is not particularly limited, and examples thereof include release agents such as long-chain alkyl group-containing polymers, silicone-based polymers (silicone-based release agents), and fluorine-based polymers (fluorine-based release agents). Examples of the substrate for the release liner include plastic films such as polyethylene terephthalate (PET) films, polyimide films, polypropylene films, polyethylene films, polycarbonate films, and polyester (excluding PET) films, and metal-deposited plastic films obtained by depositing metal on these films; papers such as Japanese paper, Western paper, craft paper, glassine paper, and fine paper; substrates made of fibrous materials such as nonwoven fabrics and cloths; and metal foils.

[0065] Examples of plastic films that are easily peelable themselves include polyethylene (low density polyethylene, linear low density polyethylene, etc.), polypropylene, ethylene-α-olefin copolymers (block copolymers or random copolymers) such as ethylene-propylene copolymers, as well as polyolefin films made of polyolefin resins consisting of mixtures of these; Teflon (registered trademark) films, etc.

[0066] The release layer formed on the surface of the substrate for the release liner can be formed by laminating or coating the plastic film material with high releasability on the substrate for the release liner.

[0067] The thickness (total thickness) of the release liner is not particularly limited, but is usually 200 μm or less, and preferably 25 to 100 μm.

[0068] (Method for evaluating the patch preparation of the present invention) The skin adhesion of the patch preparation of the present invention can be evaluated using test methods such as a tack strength test, a tensile test, a peel test (JIS Z 0237:2009, JIS K 6854), etc. For example, in a tack strength test, when the patch preparation of the present invention is peeled off from a liner and evaluated as a sensory test in which a thumb is pressed against the adhesive surface and peeled off, it is preferable that the adhesiveness is moderate when the thumb is peeled off.

[0069] In assessing the skin irritation of the patch preparation of the present invention, for example, the patch preparation of the present invention is applied to normal skin on the back of a rabbit, and the skin reaction is visually observed 24 hours after administration (30 minutes after release of the occlusion and removal of the specimen), and further 48 hours and 72 hours after administration. According to the judgment criteria of the Draize method, it is preferable that the observation score is 2 or less.

[0070] The evaluation criteria for the Draize method are the average of the individual scores of the skin reaction of each animal (observation score = (total of erythema and crust formation + edema formation) / number of observation points) according to the following scores.

[0071] (Draize method criteria) ·Erythema and crusting 0: No erythema 1: Very mild erythema 2: Obvious erythema 3: Moderate to severe erythema 4: Strong erythema ~ crust formation ·Edema formation 0: No edema 1: Very mild edema 2: Obvious edema 3: Moderate edema 4: Severe swelling

[0072] (Method of producing the percutaneously absorbable preparation of the present invention) The percutaneous absorption preparation of the present invention can be produced by known methods using pharma- ceutically acceptable additives.

[0073] [1. Method for producing the ointment of the present invention] The method for producing the ointment of the present invention is not particularly limited, and it can be produced by a generally known method, for example, the following production method.

[0074] The ointment base, compound A or a pharma- ceutically acceptable salt thereof, additive group A and additive group B are added to a suitable solvent together with other additives as necessary, and mixed thoroughly until homogeneous to form a semi-solid ointment. Examples of the solvent include water, glycerin, propylene glycol, polyethylene glycol, 1,3-butylene glycol, ethanol, isopropanol, etc.

[0075] To produce an oleaginous ointment, an oleaginous base such as fats and oils, waxes, and hydrocarbons such as paraffin is typically heated to melt, and compound A or a pharma- ceutically acceptable salt thereof, additive group A, and additive group B are added, mixed, dissolved, or dispersed, and the whole is mixed and kneaded until homogeneous. To produce a water-soluble ointment, an oleaginous base such as macrogol is typically heated to melt, and compound A or a pharma- ceutically acceptable salt thereof, additive group A, and additive group B are added, and the whole is mixed and kneaded until homogeneous.

[0076] Specifically, for example, compound A or a pharma- ceutically acceptable salt thereof is mixed with levulinic acid or a pharma- ceutically acceptable salt thereof, and additive group B, together with organic liquid components and other additives as necessary, higher alcohols such as cetanol and stearyl alcohol, higher fatty acids such as myristic acid, lauric acid, palmitic acid, stearic acid, linoleic acid, or their esters, waxes such as purified lanolin and spermaceti, surfactants such as sorbitan fatty acid esters and sucrose fatty acid esters, hydrophilic petrolatum, liquid paraffin, plastibase, and the like, and mixed under heating, kept at 50 to 100°C, and after all the components become a transparent solution, they are mixed uniformly with a homomixer. Then, the ointment can be obtained by cooling and stirring while cooling.

[0077] [2. Method for producing the patch preparation of the present invention] The method for producing the patch preparation of the present invention is not particularly limited, but it can be produced, for example, by the following production method.

[0078] The adhesive base containing an acrylic polymer, compound A or a pharma- ceutically acceptable salt thereof, levulinic acid or a pharma- ceutically acceptable salt thereof, and additive group B are added to a suitable solvent together with an organic liquid component or other additives as necessary, and mixed thoroughly until homogeneous. Examples of the solvent include ethyl acetate, toluene, hexane, 2-propanol, methanol, ethanol, water, etc. Then, when a crosslinking agent is added, the crosslinking agent is further added to this mixture and mixed thoroughly. At this time, a solvent may be added together with the crosslinking agent and mixed as necessary.

[0079] Next, the obtained mixture is applied to one side of a support or the release-treated surface of a release liner, and dried to form a pressure-sensitive adhesive layer. The application can be performed by, for example, casting, printing, or other techniques known to those skilled in the art. Then, a release liner or a support is attached to the pressure-sensitive adhesive layer to form a laminate. When crosslinking is performed, the release liner or support is attached to the pressure-sensitive adhesive layer, and then the laminate is left at 60 to 90°C, preferably 60 to 70°C, for 24 to 48 hours to promote the crosslinking reaction and form a crosslinked pressure-sensitive adhesive layer.

[0080] (Dosage of the transdermal preparation of the present invention) The dosage of the percutaneous absorption preparation of the present invention varies depending on the age, weight, symptoms, etc. of the patient, but is usually 0.1 to 500 mg, preferably 1 to 100 mg, more preferably 2 to 50 mg, and even more preferably 2 to 35 mg per day in terms of compound A for an adult. When the percutaneous absorption preparation of the present invention is a patch preparation, the size of the patch preparation of the present invention is usually 2 to 100 cm. 2 , preferably 2 to 70 cm 2 , more preferably, 4 to 50 cm 2 The patch preparation of the present invention is usually replaced at a frequency of 3 times / day to once / week, preferably once / day to once / week, and more preferably once / day.

[0081] (Concomitant medications) In the percutaneous absorption preparation of the present invention, compound A or a pharma- ceutically acceptable salt thereof can be used in combination with other drugs (hereinafter, sometimes referred to as "concomitant drugs") as long as the efficacy of the drug is not impaired. In this case, the administration time is not limited, and these drugs may be administered to the subject at the same time or at different times. Compound A or a pharma- ceutically acceptable salt thereof may also be administered in combination with the concomitant drug as a single preparation. Examples of the concomitant drug include levodopa or existing Parkinson's disease therapeutic drugs. Specific examples of existing Parkinson's disease treatment drugs include, but are not limited to, dopamine agonists (e.g., bromocriptine, pergolide, talipexole, cabergoline, pramipexole, ropinirole, rotigotine, etc.), monoamine oxidase B (MAOB) inhibitors (e.g., selegiline, rasagiline, safinamide), catechol-O-methyltransferase (COMT) inhibitors (e.g., entacapone), amantadine, apomorphine, istradefylline, anticholinergic drugs (e.g., biperiden, trihexyphenidyl, profenamine, mazaticol), tiapride, droxidopa, carbidopa, zonisamide, and the like. EXAMPLES

[0082] The present invention will be described in detail below with reference to examples and test examples, but the present invention is not limited to these examples. In the following text, "parts" or "%" all mean parts by weight or % by weight.

[0083] [Preparation of acrylic polymer A] Under an inert gas atmosphere, 55 parts of 2-ethylhexyl acrylate, 40 parts of N-vinyl-2-pyrrolidone, 5 parts of N-(2-hydroxyethyl)acrylamide, and 0.2 parts of azobisisobutyronitrile were solution-polymerized in ethyl acetate at 60° C. to prepare a solution of an acrylic polymer (acrylic polymer A).

[0084] [Preparation of acrylic polymer B] Under an inert gas atmosphere, 75 parts of 2-ethylhexyl acrylate, 22 parts of N-vinyl-2-pyrrolidone, 3 parts of acrylic acid, and 0.2 parts of azobisisobutyronitrile were solution-polymerized in ethyl acetate at 60° C. to prepare a solution of an acrylic polymer (acrylic polymer B).

[0085] <Evaluation test> In order to increase the content of Compound A in a patch preparation (tape), it is preferable to add an additive with high drug solubility, and therefore the results of measuring the saturation solubility of Compound A using various additives with different HLB values ​​are shown in Table 1. In addition, for the additives with high saturation solubility in Table 1 (i.e., lactic acid, levulinic acid, and oleic acid), solutions were prepared by combining various other additives, and the skin permeation amount of Compound A was measured for each solution, and the results are shown in Table 2.

[0086] (Test Example 1: Saturation Solubility Measurement) Various additives were weighed out into a vial, and compound A was added until it no longer dissolved, and the mixture was stirred at room temperature overnight, filtered using a 0.45 μm PTFE filter, and the concentration of compound A in the filtrate was quantified by high performance liquid chromatography (ODS column, UV detector). However, when the concentration of compound A exceeded 20%, the addition of compound A was discontinued.

[0087] (Test Example 2: Skin permeability test of solution) The skin of a miniature pig was attached to a skin permeation experiment cell (effective area 3 mmφ, receptor liquid volume 1.25 mL) so that the dermis layer side was the receptor layer, and 5 μL of a saturated solution of compound A in various additives was added, and a skin permeation test was performed for 24 hours under the condition of a receptor liquid temperature of 32 ± 1 ° C. Degassed PBS (-) solution (phosphate buffered saline) was used as the receptor liquid. After 24 hours, the receptor liquid was sampled, and the concentration of permeated compound A was quantified by high performance liquid chromatography (ODS column, UV detector).

[0088] [Table 1]

[0089] [Table 2]

[0090] According to Table 1, it was found that, among various additives, the organic acids lactic acid, levulinic acid, and oleic acid in particular exhibited high saturated solubility of compound A.

[0091] Furthermore, as shown in Table 2, for lactic acid, levulinic acid and oleic acid, which showed high saturated solubility of compound A in Table 1, solutions were prepared consisting of three or four combinations with various additives, and the skin permeation amount of compound A was measured for each solution saturated with compound A, and the following points were made clear from the results. (1) It was found that the combinations containing levulinic acid (Nos. 13 to 24) showed relatively high skin permeability of compound A compared with the combinations containing lactic acid (Nos. 1 to 12) and the combinations containing oleic acid (Nos. 25 to 36). It was an unexpected result that the combinations containing levulinic acid showed significantly superior skin permeability of compound A among the organic acids (lactic acid, levulinic acid, or oleic acid) that showed similar high saturated solubility. (2) In particular, it was found that high skin permeability of compound A was obtained in the combination of levulinic acid, polyhydric alcohol fatty acid ester, and surfactant, and among these, it was found that high skin permeability of compound A was obtained in the combination of isopropyl myristate, levulinic acid, propylene glycol fatty acid ester, and lauromacrogol (No. 15 and No. 21).

[0092] [Example 1] Acrylic polymer A 50.0 parts, compound A 20.0 parts, isopropyl myristate (hereinafter referred to as "IPM") 20.0 parts, propylene glycol monocaprylate (hereinafter referred to as "PGMC") 5.0 parts, and levulinic acid 5.0 parts were dissolved in an appropriate amount of ethyl acetate and toluene, and mixed thoroughly until the solution became uniform, and the base concentration was adjusted to 20% by weight with toluene, and the mixture was thoroughly mixed and stirred until it became uniform to obtain a coating liquid. The obtained coating liquid was applied to the release-treated surface of a release liner, which is a 75 μm thick polyethylene terephthalate (hereinafter referred to as "PET") film that had been subjected to a release treatment with a silicone-based release agent, so that the paste thickness after drying was about 150 μm, and dried to form an adhesive layer. Then, the adhesive surface of the formed adhesive layer was attached to the nonwoven side of the laminated film of the PET film and PET nonwoven fabric, which is the support, to prepare a laminate, and the patch preparation of Example 1 was obtained. The above base concentration (wt %) is the weight (g) of the coating liquid minus the weight (g) of ethyl acetate, divided by the weight (g) of the coating liquid, and multiplied by 100 (wt %).

[0093] [Example 2] The patch preparation of Example 2 was obtained in the same manner as in Example 1, except that 17.5 parts of IPM and 7.5 parts of levulinic acid were used.

[0094] [Example 3] A patch preparation of Example 3 was obtained in the same manner as in Example 1, except that 15.0 parts of IPM and 10.0 parts of levulinic acid were used.

[0095] [Example 4] Acrylic polymer C (MAS683, Cosmedi Pharmaceutical) 60.0 parts, compound A 5.0 parts, IPM 30.0 parts, levulinic acid 5.0 parts are dissolved in an appropriate amount of ethyl acetate and added, and mixed and stirred until homogeneous to obtain coating liquid. The obtained coating liquid is applied to a support made of PET film so that the paste thickness after drying is about 100 μm, and dried to form an adhesive layer. Then, the formed adhesive layer is attached to a release liner to obtain a patch preparation of Example 4.

[0096] [Example 5] The patch preparation of Example 5 was obtained in the same manner as in Example 4, except that 25.0 parts of IPM and 10.0 parts of levulinic acid were used.

[0097] [Example 6] The patch preparation of Example 6 was obtained in the same manner as in Example 4, except that 50.0 parts of acrylic polymer C, 15.0 parts of IPM, 10.0 parts of levulinic acid, 5.0 parts of 2,6-di-tert-butyl-4-methylphenol were added, and 5.0 parts of sodium thiosulfate (as anhydrous) was dissolved in an appropriate amount of water for injection and added.

[0098] [Example 6a] The patch preparation of Example 6a was obtained in the same manner as in Example 4, except that 12.5 parts of IPM, 1.5 parts of oleic acid, 10.0 parts of propylene glycol monolaurate (hereinafter referred to as "PGML"), 5.0 parts of lauromacrogol, and 1.0 part of 2,6-di-tert-butyl-4-methylphenol were added.

[0099] [Example 6b] A patch preparation of Example 6b was obtained in the same manner as in Example 6a, except that 9.0 parts of IPM and 5.0 parts of oleic acid were used.

[0100] [Comparative Example 1] A patch preparation of Comparative Example 1 was obtained in the same manner as in Example 1, except that levulinic acid was not used and 5.0 parts of lactic acid was used.

[0101] [Comparative Example 2] A patch preparation of Comparative Example 2 was obtained in the same manner as in Comparative Example 1, except that 17.5 parts of IPM and 7.5 parts of lactic acid were used.

[0102] [Comparative Example 3] A patch preparation of Comparative Example 3 was obtained in the same manner as in Comparative Example 1, except that 15.0 parts of IPM and 10.0 parts of lactic acid were used.

[0103] [Comparative Example 4] A patch preparation of Comparative Example 4 was obtained in the same manner as in Example 4, except that levulinic acid was not used and 35.0 parts of IPM was used.

[0104] [Comparative Example 5] A patch preparation of Comparative Example 5 was obtained in the same manner as in Example 4, except that levulinic acid was not used and 5.0 parts of acetic acid was added.

[0105] [Comparative Example 6] A patch preparation of Comparative Example 6 was obtained in the same manner as in Comparative Example 5, except that acetic acid was not used and 5.0 parts of lactic acid was added.

[0106] [Comparative Example 6a] A patch preparation of Comparative Example 6a was obtained in the same manner as in Comparative Example 4, except that 34.0 parts of IPM and 1.0 part of 2,6-di-tert-butyl-4-methylphenol were added.

[0107] <Evaluation test> The following tests were carried out on the patch preparations prepared in the above Examples and Comparative Examples. The results are shown in Tables 3, 4-1 and 4-2.

[0108] (Test Example 3: Skin permeability test 1 of formulation -Flow cell method-) The patch preparation was attached to the stratum corneum side of the excised skin of a hairless mouse, and attached to a flow cell for skin permeation experiments (effective area 6 mmφ) so that the dermis side was the receptor layer. A skin permeation experiment was performed for 24 hours under the conditions of a flow rate of 2.5 mL / h and a receptor liquid temperature of 32 ± 1 ° C. Degassed PBS (-) solution (phosphate buffered saline) was used as the receptor liquid. Sampling of the receptor liquid was performed over time, and the concentration of the permeated compound A was quantified by high performance liquid chromatography (ODS column, UV detector).

[0109] (Test Example 4: Skin permeability test 2 of formulation -plate method-) The patch preparation was applied to the stratum corneum side of the excised skin of a hairless mouse, and attached to a plate cell for skin permeation experiments (effective area 8 mmφ, receptor liquid volume 1.4 mL) so that the dermis layer side was the receptor layer, and a skin permeation experiment was performed for 24 hours under the condition of a receptor liquid temperature of 32 ± 1 ° C. Degassed PBS (-) solution (phosphate buffered saline) was used as the receptor liquid. After 24 hours, the receptor liquid was sampled, and the concentration of compound A that had permeated was quantified by high performance liquid chromatography (ODS column, UV detector).

[0110] [Table 3]

[0111] [Table 4-1]

[0112] [Table 4-2]

[0113] The results in Table 3 make the following points clear: (1) In comparison with Comparative Examples 1 to 3 in which lactic acid was contained in the adhesive layer, Examples 1 to 3 in which levulinic acid was contained showed a remarkable improvement in the skin permeability of Compound A, with a maximum permeation rate of 45 μg / cm 2 / h or more. (2) In addition, in Comparative Examples 1 to 3, it was found that increasing the lactic acid content decreased the skin permeability, whereas in Examples 1 to 3, increasing the levulinic acid content improved the skin permeability in an amount-dependent manner.

[0114] Furthermore, the results in Table 4-1 make the following points clear: (1) Compared with Comparative Example 4 in which the adhesive layer did not contain an organic acid, in Examples 4 to 6 in which levulinic acid was contained, the cumulative permeation amount and the maximum permeation rate were improved by about 1.5 times, indicating that the skin permeability of Compound A was improved. (2) On the other hand, in Comparative Examples 5 and 6, which contained acetic acid or lactic acid, no significant improvement in the skin permeability of Compound A was observed, as compared with Comparative Example 4, which contained no organic acid.

[0115] The results in Table 4-2 make the following points clear: (1) It was found that in Examples 6a and 6b, which contained levulinic acid, oleic acid, PGML and lauromacrogol, the skin permeability of Compound A was improved compared to Comparative Example 6a, which contained no organic acids.

[0116] [Example 7] The patch preparation of Example 7 was obtained in the same manner as in Example 1, except that PGMC was not used, and the mixture was 50.0 parts of acrylic polymer A, 20.0 parts of compound A, 25.0 parts of IPM, and 5.0 parts of levulinic acid, and the paste was applied to a thickness of approximately 100 μm.

[0117] [Example 8] The patch preparation of Example 8 was obtained in the same manner as in Example 1, except that 20.0 parts of IPM and 5.0 parts of PGMC were added and applied so that the paste thickness became approximately 100 μm.

[0118] [Comparative Example 7] A patch preparation of Comparative Example 7 was obtained in the same manner as in Example 1, except that PGMC and levulinic acid were not used, IPM was used at 30.0 parts, and the paste was applied to a thickness of approximately 100 μm.

[0119] [Comparative Example 8] A patch preparation of Comparative Example 8 was obtained in the same manner as in Example 1, except that levulinic acid was not used, 25.0 parts of IPM was used, and the paste was applied to a thickness of approximately 100 μm.

[0120] <Evaluation test> The preparations prepared in the above Examples and Comparative Examples were evaluated in Test Example 3. The results are shown in Table 5.

[0121] [Table 5]

[0122] The results in Table 5 make the following points clear: (1) In comparison with Comparative Example 7, in which the adhesive layer does not contain additive group A, in Comparative Example 8, in which only PGMC, a polyhydric alcohol fatty acid ester, is contained, almost no improvement in the skin permeability of compound A was observed. In contrast, in Example 7, in which levulinic acid is contained, a remarkable improvement in the skin permeability of compound A was observed. Furthermore, in Example 8, it was found that by combining levulinic acid with PGMC (additive group A), which alone showed almost no skin permeation enhancing effect of compound A, the skin permeability of compound A was synergistically improved.

[0123] [Example 9] Acrylic polymer B 45.0 parts, compound A 5.5 parts, IPM 31.7 parts, PGML 10.0 parts, levulinic acid 5.0 parts, lauromacrogol 1.5 parts, 2,6-di-tert-butyl-4-methylphenol 1.0 parts, sodium thiosulfate (as anhydrous) 0.08 parts dissolved in an appropriate amount of water for injection was dissolved in an appropriate amount of ethyl acetate and toluene and mixed thoroughly until the solution became uniform, and then aluminum ethyl acetoacetate diisopropylate (hereinafter referred to as "ALCH") 0.1 parts as a crosslinking agent was dissolved in an appropriate amount of ethyl acetate and acetylacetone and added, and mixed and stirred thoroughly until the solution became uniform to obtain a coating liquid. The obtained coating liquid was coated and dried in the same manner as in Example 1, except that the thickness of the paste was about 100 μm, and an adhesive layer was formed, and the adhesive layer was attached to a support to prepare a laminate. Then, the mixture was left at 70 ° C for 48 hours to prepare a crosslinked adhesive layer, and the patch preparation of Example 9 was obtained.

[0124] [Example 10] A patch preparation of Example 10 was obtained in the same manner as in Example 9, except that 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate were not used, and the ingredients were 42.1 parts of acrylic polymer B, 8.0 parts of compound A, 33.1 parts of IPM, 7.5 parts of PGML, 4.0 parts of lauromacrogol, and 0.4 parts of ALCH.

[0125] [Example 11] A patch preparation of Example 11 was obtained in the same manner as in Example 10, except that the amounts of acrylic polymer B, IPM, PGML, and lauromacrogol were changed to 34.9 parts, 26.9 parts, 14.9 parts, and 10.0 parts, respectively.

[0126] [Example 12] A patch preparation of Example 12 was obtained in the same manner as in Example 9, except that 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate were not used, and the ingredients were 39.6 parts of acrylic polymer B, 5.0 parts of compound A, 35.0 parts of IPM, 10.0 parts of PGML, 5.0 parts of levulinic acid, 5.0 parts of lauromacrogol, and 0.4 parts of ALCH.

[0127] [Example 12a] The patch preparation of Example 12a was obtained in the same manner as in Example 12, except that no lauromacrogol was used, and instead 45.0 parts of acrylic polymer B, 33.7 parts of IPM, 0.1 parts of ALCH, 1.0 part of 2,6-di-tert-butyl-4-methylphenol, and 0.13 parts of sodium thiosulfate (as anhydrous) were added.

[0128] [Example 13] A patch preparation of Example 13 was obtained in the same manner as in Example 12, except that no lauromacrogol was used, and the ingredients were 45.0 parts of acrylic polymer B, 5.5 parts of compound A, 33.2 parts of IPM, 10.0 parts of PGML, 5.0 parts of levulinic acid, 0.1 parts of ALCH, 1.0 part of 2,6-di-tert-butyl-4-methylphenol, and 0.08 parts of sodium thiosulfate (as anhydrous).

[0129] [Example 13a] The procedure of Example 13 was repeated except that the ingredients were changed to 32.2 parts of IPM, 6.0 parts of levulinic acid, and 0.13 parts of sodium thiosulfate (as anhydrous form), to obtain a patch preparation of Example 13a.

[0130] Example 13b A patch preparation of Example 13b was obtained in the same manner as in Example 13a, except that 31.2 parts of IPM and 7.0 parts of levulinic acid were used.

[0131] [Example 14] A patch preparation of Example 14 was obtained in the same manner as in Example 12, except that the ingredients were 49.9 parts of acrylic polymer B, 6.5 parts of compound A, 23.5 parts of IPM, 10.0 parts of PGML, 3.0 parts of levulinic acid, 7.0 parts of lauromacrogol, and 0.1 parts of ALCH.

[0132] [Example 15] A patch preparation of Example 15 was obtained in the same manner as in Example 12, except that PGML and lauromacrogol were not used, and the ingredients were 36.9 parts of acrylic polymer B, 8.0 parts of compound A, 49.8 parts of IPM, 5.0 parts of levulinic acid, and 0.4 parts of ALCH.

[0133] [Comparative Example 9] A patch preparation of Comparative Example 9 was obtained in the same manner as in Example 10, except that PGML, levulinic acid and lauromacrogol were not used, and 49.9 parts of acrylic polymer B, 5.0 parts of compound A, 45.0 parts of IPM, and 0.1 parts of ALCH were used.

[0134] [Comparative Example 10] A patch preparation of Comparative Example 10 was obtained in the same manner as in Comparative Example 9, except that the amounts of acrylic polymer B were 49.8 parts, compound A was 8.0 parts, IPM was 41.8 parts, and ALCH was 0.4 parts.

[0135] [Comparative Example 11] A patch preparation of Comparative Example 11 was obtained in the same manner as in Example 12, except that no lauromacrogol was used, and the ingredients were 34.9 parts of acrylic polymer B, 2.0 parts of compound A, 42.8 parts of IPM, 14.9 parts of PGML, 5.0 parts of levulinic acid, and 0.4 parts of ALCH.

[0136] <Evaluation test> The preparations prepared in the above Examples and Comparative Examples were evaluated in Test Example 3. The results are shown in Tables 6 and 7.

[0137] [Example 16] To 4.0 parts of compound A, 10.0 parts of PGML, 5.0 parts of lauromacrogol, and 5.0 parts of levulinic acid were added and mixed to dissolve, and 76.0 parts of a gelling hydrocarbon (Hicoll Gel (registered trademark), Kaneda Co., Ltd.) was added, and the mixture was mixed and kneaded to be homogeneous to obtain the ointment of Example 16.

[0138] [Example 17] An ointment of Example 17 was obtained in the same manner as in Example 16, except that 15.0 parts of IPM was added, and the mixture was adjusted to 5.0 parts of Compound A and 60.0 parts of gelling hydrocarbon (Hicoll Gel (registered trademark), Kaneda Co., Ltd.).

[0139] [Example 17a] The ointment of Example 17a was obtained in the same manner as in Example 16, except that 20.0 parts of oleic acid was added, and the total mixture was 8.0 parts of Compound A, 7.0 parts of levulinic acid, and 50.0 parts of gelling hydrocarbon (Hicoll Gel (registered trademark), Kaneda Co., Ltd.).

[0140] [Example 18] The ointment of Example 18 was obtained in the same manner as in Example 16, except that 25.0 parts of oleic acid was added, and the total mixture was 8.0 parts of Compound A, 7.0 parts of levulinic acid, and 45.0 parts of gelling hydrocarbon (Hicoll Gel (registered trademark), Kaneda Co., Ltd.).

[0141] [Example 19] The ointment of Example 19 was obtained in the same manner as in Example 16, except that 20.0 parts of oleic acid was added, and the total mixture was 10.0 parts of compound A, 7.0 parts of levulinic acid, and 48.0 parts of gelling hydrocarbon (Hicoll Gel (registered trademark), Kaneda Co., Ltd.).

[0142] [Comparative Example 12] To 8.0 parts of compound A, 42.0 parts of oleic acid were added and mixed to dissolve, and 50.0 parts of a gelling hydrocarbon (Hicoll Gel (registered trademark), Kaneda Co., Ltd.) was added and mixed and kneaded to make a homogeneous mixture to obtain an ointment of Comparative Example 12.

[0143] [Comparative Example 13] An ointment of Comparative Example 13 was obtained in the same manner as in Example 16, except that 10.0% PGML, 5.0 parts of lauromacrogol, 5.0 parts of compound A, 25.0 parts of oleic acid, and 55.0 parts of gelling hydrocarbon (Hycol Gel (registered trademark), Kaneda Co., Ltd.) were added.

[0144] <Evaluation test> The preparations prepared in the above Examples and Comparative Examples were evaluated in Test Example 4, with an effective area of ​​10.25 mmφ and a donor sample of 200 μL. The results are shown in Table 8.

[0145] [Table 6]

[0146] [Table 7]

[0147] [Table 8]

[0148] The results in Table 6 make the following points clear: (1) Compared with Comparative Examples 9 and 10 which did not contain Additive A Group, Examples 9 to 11 which contained Additive A Group showed improved cumulative permeation amount and maximum permeation rate, and a significant improvement in the skin permeability of Compound A was observed. (2) It was found that propylene glycol fatty acid esters, which are additive group A, exhibited good skin permeability of compound A when added in an amount of 7.5 to 14.9% by weight. (3) It was found that the surfactant lauromacrogol showed good skin permeability of compound A when added in an amount of 1.5 to 10.0% by weight. (4) It was found that Examples 10 and 11, which contained Additive A Group, exhibited good tack strength.

[0149] The results in Table 7 make the following points clear: (1) Compared with Comparative Example 11 in which the content of Compound A was 2.0% by weight, in Examples 12 to 15 in which the content of Compound A was 5.0% by weight or more, it was found that the cumulative permeation amount and the maximum permeation rate were improved, and the skin permeability of Compound A was improved. (2) According to Example 14, it was found that the effect of improving the skin permeability of compound A was observed when the content of levulinic acid, which is an additive group A, was 3.0% by weight or more. (3) Good tack strength was not obtained in Comparative Example 11. On the other hand, it was found that good tack strength was obtained in Example 15 containing the additive group A.

[0150] The results in Table 8 make the following points clear: (1) Compared with Comparative Example 12 not containing Additive A group, Examples 16 to 19 containing Additive A group showed improved cumulative permeation amount and maximum permeation rate, and a significant improvement in the skin permeability of Compound A was observed. (2) In addition, compared with Example 17a, the cumulative permeation amount and maximum permeation rate were improved in Example 18, and it was found that the skin permeability of Compound A was improved by increasing the content of oleic acid used in combination with levulinic acid. (3) In Comparative Example 13, which did not contain levulinic acid, only slight improvements in the cumulative permeation amount and the maximum permeation rate were observed compared to Comparative Example 12.

[0151] [Example 20] Using 39.6 parts of acrylic polymer B, 5.0 parts of compound A, 35.0 parts of IPM, 10.0 parts of PGML, 5.0 parts of levulinic acid, 5.0 parts of lauromacrogol, and 0.4 parts of ALCH, a coating liquid was obtained in the same manner as in Example 9. 0.05 parts of 2,6-di-tert-butyl-4-methylphenol was dissolved in an appropriate amount of methanol, and the previously obtained coating liquid was added so that the total amount became 100 parts, and then the patch preparation of Example 20 was obtained in the same manner as in Example 9.

[0152] [Example 21] The patch preparation of Example 21 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.13 parts of sodium thiosulfate (as anhydrous) was dissolved in an appropriate amount of water for injection and added.

[0153] [Example 22] The patch preparation of Example 22 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.62 parts of 2-mercaptobenzimidazole (hereinafter referred to as "2-MBI") was dissolved in an appropriate amount of methanol and added.

[0154] [Example 23] The patch preparation of Example 23 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.019 part of propyl gallate was dissolved in an appropriate amount of methanol and added.

[0155] [Example 24] The patch preparation of Example 24 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.002 part of α-tocopherol was dissolved in an appropriate amount of methanol and added.

[0156] [Example 25] The patch preparation of Example 25 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.2 parts of sodium sulfite (as anhydrous) was dissolved in an appropriate amount of water and added.

[0157] [Example 26] The patch preparation of Example 26 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.3 parts of sodium hydrogen sulfite was dissolved in an appropriate amount of water and added.

[0158] [Example 27] Using 48.9 parts of acrylic polymer B, 6.5 parts of compound A, 23.5 parts of IPM, 10.0 parts of PGML, 3.0 parts of levulinic acid, 7.0 parts of lauromacrogol, and 0.1 parts of ALCH, 1.0 part of 2,6-di-tert-butyl-4-methylphenol was dissolved in an appropriate amount of methanol and added, and the patch preparation of Example 27 was obtained in the same manner as in Example 9.

[0159] [Example 28] The patch preparation of Example 28 was obtained in the same manner as in Example 27, except that 2,6-di-tert-butyl-4-methylphenol was not used, 49.7 parts of acrylic polymer B was used, and 0.2 parts of 2-MBI was dissolved in an appropriate amount of methanol and added.

[0160] [Example 29] The patch preparation of Example 29 was obtained in the same manner as in Example 27, except that 48.7 parts of acrylic polymer B, 1.0 part of 2,6-di-tert-butyl-4-methylphenol was dissolved in an appropriate amount of methanol, and 0.2 parts of sodium thiosulfate (as anhydrous) was dissolved in an appropriate amount of water and added.

[0161] [Example 30] The patch preparation of Example 30 was obtained in the same manner as in Example 27, except that 48.7 parts of acrylic polymer B, 1.0 part of 2,6-di-tert-butyl-4-methylphenol and 0.2 parts of 2-MBI were dissolved in an appropriate amount of methanol and added.

[0162] [Example 31] A patch preparation of Example 31 was obtained in the same manner as in Example 9, except that 45.0 parts of acrylic polymer B, 5.5 parts of compound A, 33.2 parts of IPM, 10.0 parts of PGML, 5.0 parts of levulinic acid, 0.1 parts of ALCH, and 1.0 part of 2,6-di-tert-butyl-4-methylphenol were used, and 0.08 parts of sodium thiosulfate (as anhydrous) was dissolved in an appropriate amount of water and added.

[0163] [Example 32] A patch preparation of Example 32 was obtained in the same manner as in Example 31, except that the amount of sodium thiosulfate (as anhydrous) was 0.13 parts.

[0164] [Example 33] The procedure of Example 31 was repeated except that 31.7 parts of IPM and 1.5 parts of lauromacrogol were added to obtain a patch preparation of Example 33.

[0165] [Example 34] The procedure of Example 32 was repeated except that 31.7 parts of IPM and 1.5 parts of lauromacrogol were added to obtain a patch preparation of Example 34.

[0166] [Comparative Example 14] A patch preparation of Comparative Example 14 was obtained in the same manner as in Example 9 using 39.6 parts of acrylic polymer B, 5.0 parts of compound A, 35.0 parts of IPM, 10.0 parts of PGML, 5.0 parts of levulinic acid, 5.0 parts of lauromacrogol, and 0.4 parts of ALCH.

[0167] [Comparative Example 15] A patch preparation of Comparative Example 15 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.013 parts of L-ascorbyl palmitate was dissolved in an appropriate amount of methanol and added. [Comparative Example 16] A patch preparation of Comparative Example 16 was obtained in the same manner as in Example 20, except that 2,6-di-tert-butyl-4-methylphenol was not used and 0.1 part of L-ascorbic acid was dissolved in an appropriate amount of methanol and added.

[0168] [Comparative Example 17] A patch preparation of Comparative Example 17 was obtained in the same manner as in Example 27, except that 2,6-di-tert-butyl-4-methylphenol was not used and acrylic polymer B was used in an amount of 49.9 parts.

[0169] <Evaluation test> The preparations prepared in the above Examples and Comparative Examples were subjected to the following tests. The results are shown in Tables 10 and 11.

[0170] (Test Example 5: Stability test of formulation) Formulation samples containing various stabilizers were stored under harsh conditions (60°C for 2 weeks or 50°C for 1 month), and the stability of the formulation was evaluated based on the change in the content of compound A in the formulation and the color difference of the formulation due to storage. In addition, to evaluate the stability of the formulation against light, the formulation was stored under light exposure conditions (total illuminance 53,000 lx·h, illuminance 2,000 lx, irradiation time 26.5 h) and the compound content in the formulation was measured. The compound A content was measured using the following method.

[0171] [Content of Compound A] When HPLC analysis was performed under the following conditions, the peak area corresponding to the drug (Compound A) was calculated as area percentage % from the HPLC chart. Mobile phase A: Dilute phosphate buffer (0.05mol, pH 6.8) Mobile phase B: HPLC grade acetonitrile Detector: Ultraviolet spectrophotometer (measurement wavelength: 245 nm) Column: A stainless steel tube with an inner diameter of 4.6 mm and a length of 10 cm is filled with octadecylsilylated silica gel for HPLC (XBridge C18 or equivalent). Mobile phase delivery: The mixture ratio of mobile phase A and mobile phase B is changed as shown in Table 9 to control the concentration gradient.

[0172] [Table 9]

[0173] [Color difference] The preparation was placed on a standard white plate and measured with a colorimeter (CR-400, Konica Minolta). * The values ​​were measured.

[0174] [Table 10]

[0175] [Table 11]

[0176] The results in Table 10 make the following points clear: (1) In Comparative Example 15, in which the adhesive layer contains L-ascorbyl palmitate as a stabilizer, the content of Compound A decreased during storage under harsh conditions, as in Comparative Example 14, in which the adhesive layer does not contain a stabilizer, and the color difference index b * values ​​were also found to increase. (2) In Comparative Example 16, in which the adhesive layer contained L-ascorbic acid as a stabilizer, the decrease in the content of Compound A was slightly suppressed compared to Comparative Example 14, in which the adhesive layer contained no stabilizer. * values ​​were found to increase. (3) In contrast, in Examples 20 to 26, in which the adhesive layer contained 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-MBI, propyl gallate, α-tocopherol, sodium sulfite, or sodium hydrogen sulfite as a stabilizer, the decrease in the content of Compound A was suppressed even under harsh storage conditions, and * It was also found that the increase in the value was suppressed.

[0177] The results in Table 11 make the following points clear: (1) In Comparative Example 17, in which the adhesive layer did not contain a stabilizer, the content of Compound A decreased when the formulation was stored under harsh heat and light exposure conditions. In contrast, in Examples 27 to 34, in which the adhesive layer contained a stabilizer, the decrease in the content of Compound A was suppressed. (2) In addition, it was found that the stability of the formulation was significantly improved by combining the stabilizer 2,6-di-tert-butyl-4-methylphenol with sodium thiosulfate or 2-MBI. (3) Furthermore, it was found that the stabilizing effect of compound A in the formulation was maintained even under light exposure conditions by incorporating the stabilizers 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, and 2-MBI alone or in combination. [Industrial Applicability]

[0178] According to the present invention, it is possible to provide a tandospirone-containing transdermal preparation containing levulinic acid, which has excellent skin permeability and can maintain a sufficient blood concentration of tandospirone during use so that the pharmacological effect of tandospirone can be exerted. Furthermore, it is possible to provide a tandospirone-containing transdermal preparation (patch preparation) that has excellent storage stability and good skin permeability of the active ingredient drug tandospirone by adding a specific additive to the preparation.

[0179] This application is based on Japanese Patent Application No. 2020-026337 filed on February 19, 2020 and Japanese Patent Application No. 2020-132798 filed on August 5, 2020, the contents of which are incorporated in their entirety herein.

Claims

1. A percutaneous absorption preparation having a percutaneous absorption layer, the percutaneous absorption layer comprising: (i) tandospirone or a pharma- ceutically acceptable salt thereof; (ii) levulinic acid or a pharma- ceutically acceptable salt thereof, and (iii) Polyhydric alcohol fatty acid ester A percutaneous absorption preparation comprising:

2. The transdermal preparation according to claim 1, which is in the form of a patch preparation.

3. 3. The percutaneous absorption preparation according to claim 1, wherein the percutaneous absorption layer further contains oleic acid.

4. The percutaneous absorption preparation according to any one of claims 1 to 3, wherein the percutaneous absorption layer further contains (iv) one or more additives selected from the group consisting of 2,6-di-tert-butyl-4-methylphenol, sodium thiosulfate, 2-mercaptobenzimidazole, propyl gallate, α-tocopherol, sodium sulfite and sodium hydrogen sulfite.

5. The percutaneous absorption preparation according to any one of claims 1 to 4, wherein (i) is tandospirone.

6. The percutaneous absorption preparation according to any one of claims 1 to 5, wherein (ii) is levulinic acid.

7. The percutaneous absorption preparation according to any one of claims 4 to 6, wherein (iv) comprises 2,6-di-tert-butyl-4-methylphenol.

8. The percutaneous absorption preparation according to any one of claims 4 to 7, wherein (iv) comprises 2,6-di-tert-butyl-4-methylphenol and sodium thiosulfate.

9. The percutaneous absorption preparation according to any one of claims 1 to 8, wherein (iii) is a propylene glycol fatty acid ester.

10. The transdermal absorption preparation according to claim 9, wherein the propylene glycol fatty acid ester is propylene glycol monocaprylate, propylene glycol monolaurate, or a combination thereof.

11. The percutaneous absorption preparation according to any one of claims 1 to 10, wherein the percutaneous absorption layer further comprises a monohydric alcohol fatty acid ester.

12. The transdermal absorption preparation according to claim 11, wherein the monohydric alcohol fatty acid ester is isopropyl myristate, isopropyl palmitate, or a combination thereof.

13. The percutaneous absorption preparation according to any one of claims 1 to 12, wherein the content of (i) in 100% by weight of the percutaneous absorption layer is 0.1 to 30% by weight.

14. The percutaneous absorption preparation according to any one of claims 1 to 13, wherein the content of (ii) in 100% by weight of the percutaneous absorption layer is 0.1 to 20% by weight.

15. The percutaneous absorption preparation according to any one of claims 1 to 13, wherein the content of (ii) in 100% by weight of the percutaneous absorption layer is 3 to 10% by weight.

16. The percutaneous absorption preparation according to any one of claims 1 to 13, wherein the content of (ii) in 100% by weight of the percutaneous absorption layer is 6 to 7% by weight.

17. The percutaneous absorption preparation according to any one of claims 4 to 16, wherein the content of 2,6-di-tert-butyl-4-methylphenol as (iv) in 100% by weight of said percutaneous absorption layer is 0.001 to 10% by weight.

18. The percutaneous absorption preparation according to any one of claims 4 to 17, wherein the content of sodium thiosulfate (iv) in 100% by weight of the percutaneous absorption layer is 0.001 to 7% by weight as the anhydride.

19. The percutaneous absorption preparation according to any one of claims 4 to 18, wherein the content of 2-mercaptobenzimidazole (iv) in 100% by weight of the percutaneous absorption layer is 0.001 to 5% by weight.

20. The percutaneous absorption preparation according to any one of claims 4 to 19, wherein the content of propyl gallate (iv) in 100% by weight of the percutaneous absorption layer is 0.001 to 7% by weight.

21. The percutaneous absorption preparation according to any one of claims 1 to 20, wherein the content of the polyhydric alcohol fatty acid ester (iii) in 100% by weight of the percutaneous absorption layer is 1 to 20% by weight.

22. The percutaneous absorption preparation according to any one of claims 2 to 21, wherein the percutaneous absorption layer is an adhesive layer and the adhesive layer is provided on at least one surface of a support.

Citation Information

Patent Citations

  • Percutaneously absorbable type preparation

    JP1999079979A

  • Tandspirone agent for percutaneous administration

    JP1999228414A

  • Medicament-containing patch

    JP2006169238A

  • Adhesive and patch preparation

    JP2006241179A

  • Pharmaceutical preparation containing entecavir as an active ingredient and method for producing the same

    JP2017522285A